Probabilistic Assessment of Seismic Force Demands in Biaxially Loaded Columns in Chevron-Configured Special Concentrically Braced Frames - Burton, Henry V.; Doorandish, Nilofar; Sabol, Thomas (Engineering Journal, 2019)
Special concentrically braced frame (SCBF) columns are designed as force-controlled elements and are intended to respond elastically during moderate-to-high return-period events. When placed at the intersection of orthogonal chevron-configured braced frames with fixed beam-column connections, SCBF columns are subjected to biaxial loading, including flexural demands developed in the beams due to unbalanced tension-compression brace forces. A probabilistic assessment of the force demands in biaxially and uniaxially loaded columns in chevron-configured SCBF is presented herein. Nonlinear response history analyses are performed on three-dimensional models of 3-, 9- and 20-story SCBFs, and statistical descriptions of the results are used to investigate (1) the force demands relative to the capacity-design-based and elastic designs suggested by the American Institute of Steel Construction (AISC) Seismic Provisions, (2) the implications of the flexural demands transmitted to columns (via braced frame beams), and (3) the combinatorial effects of demands in biaxially loaded columns generated by orthogonal ground-motion components. At the maximum considered earthquake (MCE) hazard level, the median axial force demands in the biaxially loaded first-story columns of the three-story building are approximately at the level corresponding to the expected brace strength and exceed the design forces amplified by the overstrength factor. Axial flexure interaction is especially significant in the biaxially loaded columns of all three building cases. The results also show that the combinatorial effect of axial forces transmitted to the biaxially loaded columns via the orthogonal braces is generally lower in taller buildings and also depends on the demand level.